Bulk RNA-seq of skeletal muscle reveals the role of ZBED6 in sepsis-induced muscle atrophy in minipigs - Huan Liu; Wen Shi; Yanjun Zheng; Song Yang; Yihui Wang; Maosen Yang; Zhitao Yang; Enqiang Mao; Hanbing Shang; Erzhen Chen; Ying Chen (Scientific Data)
Abstract Sepsis is a severe disease and induces skeletal muscle atrophy, which has a significant impact on patients. Moreover, the onset and severity of muscle atrophy can vary across different anatomical regions during sepsis. Our previous study demonstrated that ZBED6 knockout not only promotes skeletal muscle growth under physiological conditions, but also alleviates systemic muscle atrophy during sepsis. However, its region-specific effects on sepsis-induced muscle atrophy have not been analyzed. In this study, we performed RNA sequencing for 54 samples of skeletal muscle from nine different anatomical regions from male ZBED6 knockout and wild-type (WT) minipigs subjected to sepsis. We generated 364.63 Gb of high-quality bulk RNA sequencing data from the skeletal muscle samples (approximately 6.75 Gb per sample). This dataset provided insightful gene expression information to understand the role of ZBED6 in region-specific muscle atrophy during sepsis. In addition, this dataset can be used for heterogeneity analysis between skeletal muscle tissues from multiple species or female pigs.